Validity of an isometric mid-thigh pull dynamometer in male youth athletes - Till, K.; Morris, R.; Stokes, K.; Trewartha, G.; Twist, C.; Dobbin, N.; Hunwicks, R.; Jones, B. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to investigate the validity of an isometric midthigh pull dynamometer against a criterion measure (i.e., 1,000-Hz force platform) for assessing muscle strength in male youth athletes. Twenty-two male adolescent (age 15.3 ± 0.5 years) rugby league players performed 4 isometric midthigh pull efforts (i.e., 2 on the dynamometer and 2 on the force platform) separated by 5-minute rest in a randomized and counterbalanced order. Mean bias, typical error of estimate (TEE), and Pearson correlation coefficient for peak force (PF) and peak force minus body weight (PFBW) from the force platform were validated against peak force from the dynamometer (DynoPF). When compared with PF and PFBW, mean bias (with 90% confidence limits) for DynoPF was very large (-32.4 [-34.2 to -30.6] %) and moderate (-10.0 [-12.8 to -7.2] %), respectively. The TEE was moderate for both PF (8.1 [6.3-11.2] %) and PFBW (8.9 [7.0-12.4]). Correlations between DynoPF and PF (r 0.90 [0.79-0.95]) and PFBW (r 0.90 [0.80-0.95]) were nearly perfect. The isometric midthigh pull assessed using a dynamometer underestimated PF and PFBW obtained using a criterion force platform. However, strong correlations between the dynamometer and force platform suggest that a dynamometer provides an appropriate alternative to assess isometric midthigh pull strength when a force platform is not available. Therefore, practitioners can use an isometric midthigh pull dynamometer to assess strength in the field with youth athletes but should be aware that it underestimates peak force.